Adhesive sheet with release liner

JP2026168727APending Publication Date: 2026-10-16NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025062092
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0015】 本発明のはく離ライナー付き粘着シートによれば、意図しないはく離による気泡の混入や粘着シートの変形を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026168727000001_ABST
    Figure 2026168727000001_ABST
Patent Text Reader

Abstract

The present invention provides an adhesive sheet with a release liner that can suppress the inclusion of air bubbles and deformation of the adhesive sheet due to unintended peeling. [Solution] The adhesive sheet Y with a release liner of the present invention comprises, in this order, a heavy release liner 11, a photocurable adhesive layer 21, and a light release liner 31. The adhesive layer 21 includes a cured region within 20 μm from the edge of the cross-section. The relationship between the peak peel force Xc [N / 50mm] when the heavy peel liner 11 is peeled from the adhesive layer 21 at a 90° angle and 300mm / min, and the in-plane peel force Xb [N / 50mm] when the light peel liner 31 is peeled from the adhesive layer 21 at a 90° angle and 300mm / min, satisfies Xc > Xb.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This invention relates to an adhesive sheet with a release liner. [Background technology]

[0002] A display panel has a laminated structure that includes elements such as a pixel panel, a polarizing film, a touch panel, and a cover film. In the manufacturing process of such a display panel, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure. The adhesive sheet is manufactured, for example, in a form in which both sides of the sheet are covered with a release liner (in the form of a laminated film having an adhesive layer).

[0003] In recent years, development of foldable display panels has progressed, for example, for smartphones and tablet devices. Specifically, foldable display panels can be repeatedly deformed between a bent shape and a flat, unbendable shape. In such foldable display panels, each element in the laminated structure is manufactured to be repeatedly bendable, and thin optical adhesive sheets are used to join these elements.

[0004] Regarding the optical adhesive sheet mentioned above, it is known that it can be molded into a desired shape by press working, for example, as described in Patent Document 1. [Prior art documents] [Patent Documents]

[0005] [Patent Document 1] Japanese Patent Publication No. 2014-76606 [Overview of the Initiative] [Problems that the invention aims to solve]

[0006] However, because the adhesive sheets used in foldable display panels are generally soft, when they are peeled off one release liner, the other surface of the adhesive sheet lifts away from the other release liner, and furthermore, parts of the adhesive sheet deform or air bubbles get trapped, damaging the shape and appearance of the adhesive sheet.

[0007] The present invention has been made in view of the above problems, and its objective is to provide an adhesive sheet with a peel-off liner that can suppress the inclusion of air bubbles due to unintended peeling and deformation of the adhesive sheet. [Means for solving the problem]

[0008] As a result of diligent research to achieve the above objective, the present inventors have found that an adhesive sheet with a peel liner, comprising a heavy peel liner, a photocurable adhesive layer, and a light peel liner in this order, including a cured region within 20 μm from the edge of the cross-section of the adhesive layer, and satisfying a specific peel force relationship between the heavy peel liner and the adhesive sheet and the light peel liner and the adhesive layer, can suppress the incorporation of air bubbles and deformation of the adhesive sheet due to unintended peeling.

[0009] In other words, the present invention provides an adhesive sheet with a release liner, comprising, in this order, a heavy release liner, a photocurable adhesive layer, and a light release liner, wherein the adhesive layer includes a cured region within 20 μm from the edge of the cross-section, and the relationship between the peak value of the release force (peak release force) Xc [N / 50 mm] when the heavy release liner is peeled from the adhesive layer at 90° and 300 mm / min and the in-plane release force Xb [N / 50 mm] when the light release liner is peeled from the adhesive layer at 90° and 300 mm / min satisfies Xc > Xb.

[0010] The above pressure-sensitive adhesive sheet with a release liner preferably satisfies the relationship of Xc / Xa≧2, where Xc [N / 50mm] is the peak peel force, and Xa [N / 50mm] is the in-plane peel force when the heavy release liner is peeled from the pressure-sensitive adhesive layer at 90° and 300 mm / min.

[0011] In the above pressure-sensitive adhesive sheet with a release liner, the relationship between the peak peel force Xc [N / 50mm] and the peak peel force Xc' [N / 50mm] when the heavy release liner is peeled from the cured pressure-sensitive adhesive layer at 90° and 300 mm / min after curing the pressure-sensitive adhesive layer under the condition of an integrated irradiation light quantity of 3000 mJ / cm 2 under light irradiation preferably satisfies Xc>Xc'.

[0012] The elastic modulus of the above pressure-sensitive adhesive layer at 25°C is preferably 10 to 500 kPa.

[0013] The above heavy release liner preferably has half-cut grooves formed along the end face of the pressure-sensitive adhesive layer, and the depth h of the half-cut grooves satisfies h≦0.7t with respect to the thickness t of the heavy release liner.

[0014] The thickness of the above pressure-sensitive adhesive layer is preferably 30 to 150 μm. Effects of the Invention

[0015] According to the pressure-sensitive adhesive sheet with a release liner of the present invention, it is possible to suppress air bubble entrainment and deformation of the pressure-sensitive adhesive sheet caused by unintended peeling. Brief Description of the Drawings

[0016] [Figure 1] It is a cross-sectional view of the pressure-sensitive adhesive sheet with a release liner of the present invention. [Figure 2] It is an enlarged cross-sectional view of the end portion of the pressure-sensitive adhesive sheet with a release liner of the present invention. [Figure 3] It is an enlarged cross-sectional view of the work film prepared in the preparation step. [Figure 4]This is an enlarged cross-sectional view illustrating the outer shape processing step. [Figure 5] This is an enlarged cross-sectional view illustrating the removal step. [Figure 6] This is an enlarged cross-sectional view illustrating the film reattaching step. [Figure 7] This is an enlarged cross-sectional view illustrating the cutting step. [Figure 8] This is a schematic plan view showing an example of a region of the work film after the outer shape processing step. [Mode for Carrying Out the Invention]

[0017] [Pressure-Sensitive Adhesive Sheet With Release Liner] The pressure-sensitive adhesive sheet with a release liner of the present invention includes a heavy release liner, a photocurable pressure-sensitive adhesive layer, and a light release liner in this order. The pressure-sensitive adhesive layer includes a cured region within 20 μm from the end portion of its cross section. The relationship between the peak value of the peeling force (peak peeling force) Xc [N / 50mm] when the heavy release liner is peeled from the pressure-sensitive adhesive layer at 90° and 300mm / min, and the in-plane peeling force Xa [N / 50mm] when the light release liner is peeled from the pressure-sensitive adhesive layer at 90° and 300mm / min satisfies Xc>Xa. Hereinafter, the above pressure-sensitive adhesive sheet with a release liner may be referred to as "the pressure-sensitive adhesive sheet with a release liner of the present invention".

[0018] Further, in the present invention, the light release liner means a liner that requires a smaller force to be peeled from the pressure-sensitive adhesive layer than the heavy release liner.

[0019] The pressure-sensitive adhesive sheet with a release liner of the present invention will be described with reference to Figure 1. As shown in Figure 1, the pressure-sensitive adhesive sheet Y with a release liner has a sheet shape, and includes a heavy release liner 11, a pressure-sensitive adhesive layer 21, and a light release liner 31 in this order in the thickness direction H. The pressure-sensitive adhesive layer 21 has a first surface 20a and a second surface 20b opposite to the first surface 20a. The heavy release liner 11 is in peelable contact with the first surface 20a of the pressure-sensitive adhesive layer 21. The light release liner 31 is in peelable contact with the second surface 20b.

[0020] Figure 2 is an enlarged cross-sectional view of the end of the adhesive sheet Y with a release liner. The adhesive layer 21 has an end face 21a. The heavy release liner 11 has a half-cut groove Ga formed along the end face 21a. The end face 21a forms an inclined surface that, for example, widens outward as it approaches the heavy release liner 11 in the thickness direction H. The angle α (inclination angle of the end face 21a) formed by the end face 21a and the surface of the adhesive layer 21 on the heavy release liner 11 side may be, for example, 60° to 88°. Such a shape can be formed in the external shaping process described later.

[0021] The light-peel liner 31 has an extended end 31A. The heavy-peel liner 11 has an extended end 11A. The extended ends 31A and 11A extend outward from the end face 21a of the adhesive layer 21 in the planar direction D (Figure 2), which is perpendicular to the thickness direction H. That is, the light-peel liner 31 and the heavy-peel liner 11 have outer ends 31e and 11e that extend further outward from the outer end 21e of the adhesive layer 21 in the planar direction D. From the viewpoint of suppressing edge blocking when multiple adhesive sheets Y with peel liners are stacked in the thickness direction H, the extension length d1 of the extended end 11A from the outer end 21e in the planar direction D (the direction perpendicular to the end face 21a in a plan view) is preferably 70 μm or more, more preferably 90 μm or more, and even more preferably 100 μm or more. From the viewpoint of efficiently manufacturing the adhesive sheet Y with a release liner, the extension length d1 is preferably 200 μm or less, more preferably 170 μm or less, and even more preferably 150 μm or less. The extension length d1 is the length in the surface direction D from the outer edge 21e of the adhesive layer 21 to the outer edge 11e of the heavy release liner 11, and is the maximum length of the extension end 11A. The outer edge 31e may also extend to the same position as the outer edge 11e in the surface direction D.

[0022] Furthermore, the depth h of the half-cut groove Ga is preferably such that h ≤ 0.7t, and more preferably h ≤ 0.5t, with respect to the thickness t of the heavy delamination liner 11. Satisfying h ≤ 0.7t makes it easier to suppress the fracture of the heavy delamination liner 11 itself.

[0023] Furthermore, the adhesive layer 21 includes a cured region within 20 μm from the edge of the cross-section, and preferably, the entire outer surface of the adhesive layer 21 is cured within 20 μm from the edge of the cross-section. That is, it is preferable that the end face 21a of the adhesive layer 21 does not have photocurability. With the above configuration, the heavy release liner 11 and the adhesive layer 21 become less prone to deformation as they harden, and the inclusion of air bubbles due to unintended peeling of the adhesive layer and deformation of the adhesive sheet when peeling the heavy release liner 11 from the adhesive layer 21 can be suppressed. In addition, when comparing the surface hardness (H1) at 25°C measured by nanoindentation of the hardened region with the surface hardness (H2) at 25°C measured by nanoindentation of an uncured region more than 20 μm away from the edge of the adhesive layer 21, the ratio of H1 to H2 (H1 / H2) is preferably 1.50 or more, and more preferably 2.0 or more. The upper limit may be 10 or less. In this invention, if the above ratio is 0.8 or less, it can be evaluated as softened, and if it is 1.5 or more, it can be evaluated as hardened.

[0024] In this invention, the nanoindentation method is performed in accordance with ISO 14577. Specifically, the nanoindentation method involves a process of pressing an indenter into a sample set on a stage (load application process) and a subsequent process of withdrawing the indenter from the sample (unloading process). During this series of processes, the load acting between the indenter and the sample, and the relative displacement of the indenter relative to the sample are measured (load-displacement measurement). This makes it possible to obtain a load-displacement curve. From this load-displacement curve, various physical properties (hardness and modulus of elasticity, etc.) of the surface of the sample can be determined based on nanometer-scale measurements. For load-displacement measurement using the nanoindentation method, for example, a nanoindenter (product name "Triboindenter", manufactured by Hysitron) can be used. In this measurement, the measurement mode is single-indentation measurement, the measurement temperature is 25°C, the indenter used is a Berkovich (triangular pyramidal) type diamond indenter (diameter 20 μm), the maximum indentation depth (maximum displacement hmax) of the indenter into the sample during the load application process is 4 μm, the indentation speed of the indenter is 1000 nm / second, and the withdrawal speed of the indenter from the sample during the unloading process is 1000 nm / second. The obtained measurement data is then processed using the dedicated analysis software (Ver. 9.4.0.1) of "TI950 Triboindenter". Specifically, based on the obtained load (F)-displacement (h) curve, the maximum load Fmax (load acting on the indenter at maximum displacement hmax), the contact projection area Ap (projected area of ​​the contact region between the indenter and the sample at maximum load), and the surface hardness of the sample (=Fmax / Ap) are calculated.

[0025] In the adhesive sheet Y with a release liner, the relationship between the peak value of the peeling force (peak peeling force) Xc [N / 50mm] when the adhesive layer 21 is peeled from the heavy release liner 11 at a 90° angle and 300mm / min, and the in-plane peeling force Xb [N / 50mm] when the light release liner 31 is peeled from the adhesive layer 21 at a 90° angle and 300mm / min, satisfies Xc > Xb. In particular, in the adhesive sheet Y with a release liner, when the edges of the cross-section of the adhesive layer 21 harden, the heavy release liner 31 and the adhesive layer 21 harden, making them less prone to deformation, thus making it easier to satisfy Xc > Xb. By satisfying Xc > Xb, the adhesive sheet Y with a release liner can suppress unintended peeling of the adhesive layer 21 on the heavy release liner 31 side when the light release liner 11 is peeled from the adhesive layer 21, thereby preventing the inclusion of air bubbles and deformation. Furthermore, it is preferable that Xc / Xb ≥ 230, and more preferably that Xc / Xb ≥ 250.

[0026] Furthermore, when peeling the adhesive layer from the release liner, the peeling force may increase sharply from the start of peeling, reach a peak, and then gradually decrease and converge to a constant value. In this invention, the peak peeling force is the peeling force at the peak, and the in-plane peeling force is the peeling force after the convergence.

[0027] In the adhesive sheet Y with a release liner, it is preferable that the relationship between the peak release force Xc [N / 50mm] and the in-plane release force Xa [N / 50mm] when the heavy release liner 11 is peeled from the adhesive layer 21 at a 90° angle and 300mm / min satisfies Xc / Xa≧2, more preferably Xc / Xa≧2.5, and even more preferably Xc / Xa≧3.4. In particular, the hardening of the edges of the cross-section of the adhesive layer 21 makes it easier to satisfy Xc / Xa≧2. By satisfying Xc / Xa≧2, the peak release force of the heavy release liner 11 can be sufficiently high in the adhesive sheet Y with a release liner, which makes it easier to suppress the inclusion of air bubbles and deformation due to unintended peeling when peeling the light release liner 31 from the adhesive layer 21.

[0028] Furthermore, the above peak peeling force Xc [N / 50mm] and the integrated light intensity of 3000 mJ / cm² irradiated onto the adhesive layer 21 are also considered. 2 It is preferable that the relationship between the peak peel force Xc' [N / 50mm] when the heavy peel liner 11, cured by light irradiation, is peeled from the cured adhesive layer 21' at a 90° angle and 300mm / min, satisfies Xc > Xc'. Satisfying Xc > Xc' reduces the peak peel force when peeling the heavy peel liner 11 from the adhesive layer 21 due to curing. This reduces the risk of deformation of the adhesive layer 21 and increased susceptibility to air bubbles when peeling the light peel liner 31 of the adhesive sheet Y with a peel liner, attaching the peel surface to the adherend, and then peeling off the heavy peel liner 11. Furthermore, it is preferable that 0.8 ≥ Xc' / Xc is satisfied, and more preferable that 0.6 ≥ Xc' / Xc is satisfied.

[0029] The thickness of the adhesive sheet Y with a release liner is preferably 50 μm or more, more preferably 70 μm or more, and even more preferably 90 μm or more. Furthermore, from the viewpoint of thinning, it is preferably 500 μm or less, more preferably 450 μm or less, and even more preferably 300 μm or less.

[0030] (Heavy peeling liner) Examples of materials for the heavy peel-off liner 10 include polyester, polyolefin, and polycarbonate. Examples of polyester include polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate. Examples of polyolefin include polyethylene, polypropylene, and cycloolefin polymer (COP). The heavy peel-off liner 10 is peelably in contact with the first surface 20a of the adhesive layer 20. The surface of such a heavy peel-off liner 10 (the surface on the adhesive layer 20 side) is preferably subjected to a peel-off treatment. Examples of peel-off treatments include silicone peel-off treatment and fluorine peel-off treatment.

[0031] The thickness of the heavy release liner 10 is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring a protective function against the adhesive layer 20. The thickness of the heavy release liner 10 is preferably 150 μm or less, more preferably 120 μm or less, and even more preferably 100 μm or less, from the viewpoint of thinning the adhesive sheet Y with the release liner.

[0032] (Adhesive layer) The adhesive layer 20 is photocurable, and known or conventional photocurable adhesive layers can be used. Preferably, the adhesive layer 20 is a solvent-free adhesive layer containing a photopolymerizable polymer as the base polymer. Specifically, the adhesive layer 20 is preferably a sheet-like pressure-sensitive adhesive (solvent-free adhesive sheet) formed from a solvent-free adhesive composition. Therefore, it is preferable that the adhesive layer 20 (solvent-free adhesive composition) contains at least a photopolymerizable polymer as the base polymer. A photopolymerizable polymer is a polymer formed by a polymerization method in which the polymerization reaction of polymerizable components is advanced by irradiation with active energy rays such as ultraviolet light.

[0033] The adhesive layer 20 can be formed from an adhesive composition. Preferably, the adhesive composition is a solvent-free adhesive composition. A solvent-free adhesive composition eliminates the need for a step in the manufacturing process of the adhesive layer by volatilizing and removing the solvent from the coating film of the composition. Therefore, an adhesive sheet equipped with the adhesive layer is suitable for reducing environmental impact.

[0034] The base polymer is an adhesive component that exhibits tackiness in the adhesive layer 20. In this specification, the base polymer refers to the main polymer component in the adhesive constituting the adhesive layer, for example, the polymer component present in more than 50% by mass. The content of the base polymer in the adhesive layer is preferably 60% by mass or more, more preferably 75% by mass or more (for example, 75 to 99.9% by mass), and even more preferably 85% by mass or more (for example, 85 to 99.9% by mass), based on 100% by mass of the total amount of the adhesive layer.

[0035] The weight-average molecular weight of the above base polymer is preferably 100,000 or more, more preferably 300,000 or more, and even more preferably 500,000 or more, from the viewpoint of ensuring cohesive force in the adhesive layer 20. The weight-average molecular weight is preferably 5,000,000 or less, more preferably 3,000,000 or less, and even more preferably 2,000,000 or less. The weight-average molecular weight is measured by gel permeation chromatography (GPC) and calculated on a polystyrene basis.

[0036] The above-mentioned base polymer is not particularly limited, but examples include acrylic polymers, rubber polymers (such as natural rubber polymers and synthetic rubber polymers), silicone polymers, polyester polymers, polyurethane polymers, polyamide polymers, epoxy polymers, vinyl alkyl ether polymers, and fluorine polymers. One or more of the above-mentioned base polymers may be used. From the viewpoint of ensuring good transparency and tackiness in the adhesive layer 20, it is preferable to include an acrylic polymer as the base polymer.

[0037] The above-mentioned acrylic polymer is a polymer that contains an acrylic monomer (a monomer having a (meth)acryloyl group in its molecule) as a monomer component constituting the polymer. That is, the above-mentioned acrylic polymer contains constituent units derived from an acrylic monomer. Note that only one type of acrylic polymer may be used, or two or more types may be used. Furthermore, the above-mentioned acrylic polymer may contain only one type of acrylic monomer as a monomer component, or two or more types may be contained. In this specification, "(meth)acrylic" refers to "acrylic" and / or "methacrylic" (either one or both of "acrylic" and "methacrylic"), and the same applies to other terms.

[0038] In this specification, the term "monomer component" refers to a compound having only one polymerizable functional group and does not include compounds having two or more polymerizable functional groups, such as polyfunctional (meth)acrylates.

[0039] The above acrylic polymer is a polymer of monomer components containing more than 50% by mass of (meth)acrylic acid ester. The above (meth)acrylic acid ester is not particularly limited, but alkyl (meth)acrylic acid ester is preferred, and alkyl (meth)acrylic acid ester having 1 to 20 carbon atoms in the alkyl group is more preferred.

[0040] Examples of the alkyl (meth)acrylate esters mentioned above include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, pentyl (meth)acrylate, n-hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate (i.e., lauryl (meth)acrylate), isotridecyl (meth)acrylate, and tetradecyl (meth)acrylate. Only one alkyl (meth)acrylate ester may be used, or two or more may be used. The alkyl (meth)acrylate is preferably at least one selected from the group consisting of 2-ethylhexyl acrylate (2EHA), lauryl acrylate (LA), and n-butyl acrylate (BA).

[0041] The content of the above alkyl (meth)acrylate is not particularly limited, but from the viewpoint of appropriately exhibiting basic properties such as tackiness in the adhesive layer 20, it is preferably 60% by mass or more, more preferably 70% by mass or more (for example, 70 to 99.9% by mass), and even more preferably 90% by mass or more (for example, 90 to 99.9% by mass), based on the total amount (100% by mass) of the monomer components constituting the above acrylic polymer. Furthermore, the above content may be, for example, 99% by mass or less.

[0042] The above-mentioned acrylic polymer may contain, in addition to the above-mentioned alkyl (meth)acrylate, copolymerizable functional group-containing monomers (copolymerizable functional group-containing monomers) as monomer components constituting the polymer. In other words, the acrylic polymer may contain functional group-containing monomers as constituent monomer components. Note that only one type of functional group-containing monomer may be used, or two or more types may be used.

[0043] As the above-mentioned functional group-containing monomers, hydroxyl group-containing monomers are preferred. When an acrylic polymer contains a hydroxyl group-containing monomer as a monomer unit, polymerization of the constituent monomer components becomes easier, and the cohesive force can be increased. Furthermore, the interaction with the adherend interface can be enhanced. As a result, strong adhesion can be easily obtained.

[0044] The above-mentioned hydroxyl group-containing monomers refer to monomers that have at least one hydroxyl group in their molecule. Furthermore, monomers that have at least one hydroxyl group and at least one carboxyl group in their molecule are carboxyl group-containing monomers and not hydroxyl group-containing monomers. The above-mentioned hydroxyl group-containing monomers are not particularly limited, but specifically include, for example, hydroxyl group-containing (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl) (meth)acrylate; vinyl alcohol, allyl alcohol, etc. In particular, as the hydroxyl group-containing monomer, hydroxyl group-containing (meth)acrylic acid esters are preferred from the viewpoint of easily obtaining good cohesive force and improving adhesive reliability at high temperatures, and more preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (HEA), 2-hydroxypropyl (meth)acrylate (HPA), and 4-hydroxybutyl acrylate (4HBA). Note that only one type of hydroxyl group-containing monomer may be used, or two or more types may be used.

[0045] The content (ratio) of the above hydroxyl group-containing monomer relative to the total amount (100% by mass) of monomer components constituting the acrylic polymer is not particularly limited, but from the viewpoint of introducing a crosslinked structure into the acrylic polymer and ensuring cohesive force in the adhesive layer 20, it is preferably 1% by mass or more, more preferably 2% by mass or more, and even more preferably 3% by mass or more. From the viewpoint of adjusting the polarity of the acrylic polymer, the above content ratio is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less.

[0046] Furthermore, nitrogen atom-containing monomers are preferred as the functional group-containing monomers. When an acrylic polymer contains nitrogen atom-containing monomers as monomer units, it becomes easier to obtain appropriate cohesive force, which in turn makes it easier to obtain strong adhesion and excellent foaming resistance.

[0047] A nitrogen atom-containing monomer refers to a monomer that has at least one nitrogen atom within its molecule (one molecule). However, the above-mentioned hydroxyl group-containing monomer does not include nitrogen atom-containing monomers. In other words, in this specification, monomers having both a hydroxyl group and a nitrogen atom in their molecule are included in nitrogen atom-containing monomers. Furthermore, a monomer having at least one nitrogen atom and at least one carboxyl group in its molecule is a carboxyl group-containing monomer and not a nitrogen atom-containing monomer.

[0048] From the viewpoint of exhibiting strong adhesive properties, N-vinylcyclic amides, (meth)acrylamides, etc., are preferred as the nitrogen atom-containing monomers mentioned above. Note that only one type of nitrogen atom-containing monomer may be used, or two or more types may be used.

[0049] As the above N-vinyl cyclic amide, an N-vinyl cyclic amide represented by the following formula (1) is preferred from the viewpoint of easily obtaining good cohesive force and easily obtaining adhesive reliability at high temperatures. [ka] (In formula (1), R 1 (This indicates a divalent organic group.)

[0050] R in equation (1) above 1 is a divalent organic group, preferably a divalent saturated hydrocarbon group or an unsaturated hydrocarbon group, and more preferably a divalent saturated hydrocarbon group (for example, an alkylene group having 3 to 5 carbon atoms).

[0051] From the viewpoint of exhibiting even stronger adhesiveness, the N-vinyl cyclic amide represented by formula (1) above is preferably N-vinyl-2-pyrrolidone (NVP), N-vinyl-2-piperidone, N-vinyl-2-caprolactam, N-vinyl-3-morpholinone, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholindione, more preferably N-vinyl-2-pyrrolidone and N-vinyl-2-caprolactam, and even more preferably N-vinyl-2-pyrrolidone.

[0052] Examples of the above (meth)acrylamides include (meth)acrylamide, N-alkyl(meth)acrylamide, and N,N-dialkyl(meth)acrylamide. Examples of the above N-alkyl(meth)acrylamides include N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, Nn-butyl(meth)acrylamide, and N-octylacrylamide. Furthermore, the above N-alkyl(meth)acrylamides also include (meth)acrylamides having an amino group, such as dimethylaminoethyl(meth)acrylamide, diethylaminoethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Examples of the above-mentioned N,N-dialkyl(meth)acrylamides include N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide.

[0053] Furthermore, the above-mentioned (meth)acrylamides also include, for example, various N-hydroxyalkyl (meth)acrylamides. Examples of the above-mentioned N-hydroxyalkyl (meth)acrylamides include N-methylol(meth)acrylamide, N-(2-hydroxyethyl)(meth)acrylamide, N-(2-hydroxypropyl)(meth)acrylamide, N-(1-hydroxypropyl)(meth)acrylamide, N-(3-hydroxypropyl)(meth)acrylamide, N-(2-hydroxybutyl)(meth)acrylamide, N-(3-hydroxybutyl)(meth)acrylamide, N-(4-hydroxybutyl)(meth)acrylamide, and N-methyl-N-2-hydroxyethyl(meth)acrylamide.

[0054] Furthermore, the above-mentioned (meth)acrylamides also include, for example, various N-alkoxyalkyl(meth)acrylamides. Examples of the above-mentioned N-alkoxyalkyl(meth)acrylamides include N-methoxymethyl(meth)acrylamide and N-butoxymethyl(meth)acrylamide.

[0055] Furthermore, nitrogen atom-containing monomers other than the above N-vinyl cyclic amides and (meth)acrylamides include, for example, amino group-containing monomers such as (meth)aminoethyl acrylate, (meth)dimethylaminoethyl acrylate, (meth)dimethylaminopropyl acrylate, and (meth)butylaminoethyl acrylate; cyano group-containing monomers such as acrylonitrile and methacrylonitrile; (meth)acryloylmorpholine, N-vinylpiperazine, N-vinylpyrrole, N-vinylimidazole, N-vinylpyrazine, N-vinylmorpholine, N-vinylpyrazole, vinylpyridine, vinylpyrimidine, vinyloxazole, vinylisoxazole, vinylthiazole, vinylisothiazole, vinylpyridazine, (meth)acryloylpyrrolidone, (meth)acryloylpyrrolidine, (meth)acryloylpiperidine, N- Examples include heterocyclic monomers such as methylvinylpyrrolidone; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; itaconimide monomers such as N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-laurylitaconimide, and N-cyclohexylitaconimide; imide group-containing monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; and isocyanate group-containing monomers such as 2-(meth)acryloyloxyethyl isocyanate.

[0056] The content (percentage) of the nitrogen atom-containing monomer relative to the total amount (100% by mass) of monomer components constituting the acrylic polymer is not particularly limited, but from the viewpoint of ensuring cohesive force in the adhesive layer 20 and ensuring adhesion force to the substrate in the adhesive layer 20, it is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more. From the viewpoint of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer, the above content is preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 8% by mass or less.

[0057] In addition to the nitrogen atom-containing monomers and hydroxyl group-containing monomers mentioned above, copolymerizable monomers in acrylic polymers include alicyclic structure-containing monomers [e.g., cyclopropyl (meth)acrylate, cyclobutyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate]; and alkoxyalkyl esters of (meth)acrylates [e.g., 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, methoxytriethylene glycol (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxyethyl (meth)acrylate]; Examples include propyl, 4-methoxybutyl (meth)acrylate, 4-ethoxybutyl (meth)acrylate, etc.; epoxy group-containing monomers [e.g., glycidyl (meth)acrylate, methylglycidyl (meth)acrylate, etc.]; sulfonic acid group-containing monomers [e.g., sodium vinylsulfonate, etc.]; phosphate group-containing monomers; (meth)acrylate esters having aromatic hydrocarbon groups [e.g., phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, etc.]; vinyl esters [e.g., vinyl acetate, vinyl propionate, etc.]; aromatic vinyl compounds [e.g., styrene, vinyltoluene, etc.]; olefins or dienes [e.g., ethylene, propylene, butadiene, isoprene, isobutylene, etc.]; vinyl ethers [e.g., vinyl alkyl ether, etc.]; vinyl chloride, etc.

[0058] The acrylic polymer preferably contains no or substantially no carboxy group-containing monomer as a monomer component constituting the polymer. By containing no or substantially no carboxy group-containing monomer, in a touch panel laminated with an optical member (touch sensor film) having metal wiring such as a metal mesh film or a silver nanowire film, the effect of preventing corrosion to the metal wiring can be obtained. The content of the carboxy group-containing monomer is 1 ng / cm relative to the total amount of monomer components constituting the polymer 2 or less (for example, 0 to 1 ng / cm 2 ) is preferred, more preferably 0.8 ng / cm 2 or less (for example, 0 to 0.8 ng / cm 2 ), still more preferably 0.5 ng / cm 2 or less (for example, 0 to 0.5 ng / cm 2 ) can be said to be substantially not contained. Examples of the carboxy group-containing monomer include (meth)acrylic acid, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid and the like, and the carboxy group-containing monomer also includes, for example, acid anhydride group-containing monomers such as maleic anhydride and itaconic anhydride.

[0059] The content (ratio) of the functional group-containing monomer is not particularly limited, but from the viewpoint of exhibiting appropriate adhesiveness, it is preferably 5 to 40% by mass, more preferably 7 to 35% by mass, and still more preferably 10 to 30% by mass, relative to the total amount (100% by mass) of the monomer components constituting the acrylic polymer. Further, the total content of the hydroxyl group-containing monomer and the nitrogen atom-containing monomer is preferably within the above range.

[0060] When the above-mentioned acrylic polymer contains hydroxyl group-containing monomers and nitrogen atom-containing monomers as functional group-containing monomer components constituting the polymer, the content of the functional group-containing monomer that is most abundant among the hydroxyl group-containing monomers and nitrogen atom-containing monomers is preferably 60% by mass or more, more preferably 65% ​​by mass or more (for example, 65 to 99.9% by mass), and even more preferably 70% by mass or more (for example, 70 to 99.9% by mass), based on the total amount (100% by mass) of the hydroxyl group-containing monomers and nitrogen atom-containing monomers.

[0061] The glass transition temperature (Tg) calculated from the monomer components constituting the above-mentioned acrylic polymer is preferably 0°C or lower, more preferably -10°C or lower, and even more preferably -20°C or lower, from the viewpoint of ensuring the softness of the adhesive layer 20. The above-mentioned glass transition temperature (Tg) may be, for example, -80°C or higher.

[0062] The glass transition temperature (Tg) mentioned above is a calculated glass transition temperature derived from Fox's formula. This calculated glass transition temperature is determined based on the type and amount of each monomer component constituting the acrylic polymer, and therefore can be adjusted by selecting the type and amount of each monomer component.

[0063] The calculated glass transition temperature (calculated Tg) can be calculated from Fox's equation [1] below. 1 / Calculation Tg=W1 / Tg(1)+W2 / Tg(2)+···+Wn / Tg(n) [1] Here, W1, W2, ...Wn represent the weight fractions (weight %) of monomer components (1), (2), ...monomer component (n) that constitute the acrylic polymer, relative to the total monomer components, and Tg(1), Tg(2), ...Tg(n) represent the glass transition temperatures (unit: absolute temperature: K) of the homopolymer of monomer components (1), (2), ...monomer component (n).

[0064] In this specification, "glass transition temperature (Tg) of homopolymer" (sometimes simply referred to as "Tg of homopolymer") means "glass transition temperature (Tg) of the homopolymer of the monomer," and specifically, the numerical value is given in the "Polymer Handbook" (3rd edition, John Wiley & Sons, Inc., 1987). For monomer homopolymers not listed in the above literature, the Tg refers to the value obtained by, for example, the following measurement method (see Japanese Patent Publication No. 2007-51271), except for monomers having a polyorganosiloxane skeleton. That is, 100 parts by mass of monomer, 0.2 parts by mass of 2,2'-azobisisobutyronitrile, and 200 parts by mass of ethyl acetate as a polymerization solvent are added to a reactor equipped with a thermometer, stirrer, nitrogen inlet tube, and reflux condenser, and the mixture is stirred for 1 hour while introducing nitrogen gas. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and the reaction is carried out for 10 hours. Next, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid content of 33% by mass. Then, this homopolymer solution is cast onto a release liner and dried to produce a test sample (sheet-like homopolymer) with a thickness of approximately 2 mm. This test sample is then punched out into a disc shape with a diameter of 7.9 mm, sandwiched between parallel plates, and the viscoelasticity is measured using a viscoelasticity tester (product name "ARES", manufactured by Rheometrics) in shear mode while applying a shear strain of 1 Hz at a frequency of -70 to 150°C and a heating rate of 5°C / min. The peak top temperature of tanδ is taken as the Tg of the homopolymer.

[0065] The above-mentioned acrylic polymer may contain structural units derived from polyfunctional monomers copolymerizable with monomer components that form the acrylic polymer, in order to form a crosslinked structure within its polymer backbone. Examples of the above-mentioned polyfunctional monomers include polyfunctional (meth)acrylates such as hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol hexa(meth)acrylate, as well as monomers having a (meth)acryloyl group and other reactive functional groups in the molecule, such as epoxy (meth)acrylate (e.g., polyglycidyl (meth)acrylate), polyester (meth)acrylate, and urethane (meth)acrylate. Only one of the above-mentioned polyfunctional monomers may be used, or two or more may be used. The content of the polyfunctional monomer relative to the total amount (100 parts by mass) of monomer components constituting the above acrylic polymer is preferably 40 parts by mass or less, and more preferably 30 parts by mass or less. The above content may be, for example, 1 part by mass or more.

[0066] When polymerizing the above-mentioned base polymer (especially acrylic polymers), polymerization initiators such as thermal polymerization initiators and photopolymerization initiators (photoinitiators) may be used depending on the type of polymerization reaction, and the use of photopolymerization initiators is preferred. Note that only one polymerization initiator may be used, or two or more may be used.

[0067] The above-mentioned photopolymerization initiators are not particularly limited, but examples include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and the like. Note that one or more photopolymerization initiators may be used.

[0068] Examples of the above-mentioned benzoin ether-based photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, 2,2-dimethoxy-1,2-diphenylethane-1-one, and anisole methyl ether. Examples of the above-mentioned acetophenone-based photopolymerization initiators include 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of the above-mentioned α-ketol-based photopolymerization initiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of the above-mentioned aromatic sulfonyl chloride-based photopolymerization initiators include 2-naphthalenesulfonyl chloride. Examples of the above-mentioned photoactive oxime-based photopolymerization initiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of the above-mentioned benzoin-based photopolymerization initiators include benzoin. Examples of the above-mentioned benzyl-based photopolymerization initiators include benzyl. Examples of the above-mentioned benzophenone-based photopolymerization initiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexylphenyl ketone. Examples of the above-mentioned ketal-based photopolymerization initiators include benzyldimethylketal. Examples of the above-mentioned thioxanthone-based photopolymerization initiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, etc.

[0069] The amount of the photopolymerization initiator used when polymerizing the above-mentioned base polymer (especially acrylic polymer) is not particularly limited, but for example, it is preferably 0.001 to 1 part by mass, and more preferably 0.01 to 0.50 parts by mass, per 100 parts by mass of the total monomer units (total amount of monomer components constituting the base polymer) of the above-mentioned base polymer (especially acrylic polymer).

[0070] Furthermore, the above-mentioned thermal polymerization initiator is not particularly limited, but examples include azo polymerization initiators, peroxide polymerization initiators (e.g., dibenzoyl peroxide, tert-butyl permaleate, etc.), and redox polymerization initiators. Among these, the azo polymerization initiator disclosed in Japanese Patent Application Publication No. 2002-69411 is preferred. Examples of the above-mentioned azo polymerization initiators include 2,2'-azobisisobutyronitrile (hereinafter sometimes referred to as "AIBN"), 2,2'-azobis-2-methylbutyronitrile (hereinafter sometimes referred to as "AMBN"), 2,2'-azobis(2-methylpropionic acid)dimethyl, and 4,4'-azobis-4-cyanovaleric acid.

[0071] The amount of the thermal polymerization initiator used when polymerizing the above-mentioned base polymer (especially acrylic polymer) is not particularly limited, but for example, in the case of the above-mentioned azo polymerization initiator, it may be 0.05 to 0.5 parts by mass or 0.1 to 0.3 parts by mass per 100 parts by mass of the total monomer units (total amount of monomer components constituting the base polymer) of the base polymer (especially acrylic polymer).

[0072] The above-mentioned adhesive composition is not particularly limited, but examples include compositions containing the above-mentioned base polymer (particularly acrylic polymer); compositions containing a mixture of monomer components constituting the above-mentioned base polymer (sometimes referred to as a "monomer mixture") or a partially polymer thereof. Examples of the former include so-called water-dispersible compositions (emulsion-type compositions), and examples of the latter include so-called active energy ray-curable compositions. Among these, adhesive compositions containing the above-mentioned monomer mixture or a partially polymer thereof are preferred.

[0073] The above monomer mixture may consist of a single monomer component or two or more monomer components. Furthermore, the above "partially polymerized product" may also be referred to as a "prepolymer" or "syrup," and means a composition in which one or more monomer components of the above monomer mixture are partially polymerized.

[0074] The above adhesive composition may contain a photopolymerization initiator in addition to those contained in the base polymer (particularly acrylic polymer). That is, a photopolymerization initiator may be added when preparing the above adhesive composition. As a photopolymerization initiator other than those contained in the base polymer, the photopolymerization initiators exemplified for use with the base polymer above can be used. Note that only one type of photopolymerization initiator other than those contained in the base polymer may be used, or two or more types may be used.

[0075] The content (percentage) of photopolymerization initiators other than those contained in the base polymer (particularly acrylic polymer) in the above adhesive composition is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, even more preferably 0.05 parts by mass or more, and may be 0.1 parts by mass or more, per 100 parts by mass of the base polymer (particularly acrylic polymer). Furthermore, the above content (percentage) is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, and may be 0.5 parts by mass or less, per 100 parts by mass of the base polymer.

[0076] Furthermore, it is preferable that the above adhesive composition does not contain or substantially contains organic solvents. The above organic solvent is not particularly limited as long as it is an organic compound used as a solvent, but examples include hydrocarbon solvents such as cyclohexane, hexane, and heptane; aromatic solvents such as toluene and xylene; ester solvents such as ethyl acetate and methyl acetate; ketone solvents such as acetone and methyl ethyl ketone; and alcohol solvents such as methanol, ethanol, butanol, and isopropyl alcohol. Note that one or more of the above organic solvents may be used.

[0077] In the above-mentioned adhesive composition, "substantially free of organic solvents" means that organic solvents are not actively incorporated, except in cases where organic solvents are inevitably mixed in. Specifically, an adhesive composition in which the content of organic solvents is 1.0% by mass or less (preferably 0.5% by mass or less, and more preferably 0.2% by mass or less) relative to the total amount of the adhesive composition (100% by mass) can be said to be substantially free of organic solvents.

[0078] The adhesive layer 20 may be formed from the adhesive composition and further modified with a photopolymerization initiator. Therefore, the origin of the photopolymerization initiator contained in the adhesive layer 20 is not particularly limited, but it may be (i) a photopolymerization initiator contained in the base polymer (especially an acrylic polymer), (ii) a photopolymerization initiator other than (i) added to the adhesive composition, or (iii) a photopolymerization initiator added after the adhesive layer 20 has been formed from the adhesive composition. In (iii), the photopolymerization initiator added may be one of the photopolymerization initiators exemplified for use with the acrylic polymer described above. In (iii), only one type of photopolymerization initiator may be used, or two or more types may be used.

[0079] In (iii), the photopolymerization initiator can be added to the adhesive layer 20 by coating (applying) a solution of the photopolymerization initiator to one surface of the adhesive layer 20. The solution may be coated to the first surface 20a of the adhesive layer 20, or to the second surface 20b of the adhesive layer 20. The solution of the photopolymerization initiator is not particularly limited as long as it is liquid, can be applied to the adhesive layer 20, and penetrates it. For example, if the photopolymerization initiator is liquid, the photopolymerization initiator itself may be applied as a solution, or it may be applied as a solution obtained by dissolving the photopolymerization initiator in a solvent. By adding it in this way, the photopolymerization initiator in the solution penetrates into the adhesive layer 20 in the thickness direction on the one surface of the adhesive layer 20. As a result, the photopolymerization initiator becomes dissolved in the adhesive layer 20.

[0080] Furthermore, a concentration gradient may be formed in the thickness direction as the photopolymerization initiator penetrates the adhesive layer 20. That is, the concentration of the photopolymerization initiator on the side coated with the above solution (one of the above sides) may be higher than that on the opposite side (the side opposite to the one of the above sides).

[0081] Subsequently, by drying the adhesive layer 20, the adhesive layer 20 returns to a state similar to that before the above solution was applied. Therefore, differences in physical properties between the front and back surfaces of the adhesive layer 20 and changes in adhesive strength can be further suppressed. Once the adhesive layer 20 is dried, the penetration of the photopolymerization initiator into the adhesive layer 20 stops, and the concentration gradient of the photopolymerization initiator is fixed.

[0082] The content (percentage) of the photopolymerization initiator in the adhesive layer 20 is not particularly limited, but is preferably 0.01 parts by mass or more, more preferably 0.02 parts by mass or more, even more preferably 0.05 parts by mass or more, and may be 0.1 parts by mass or more, per 100 parts by mass of the base polymer (especially acrylic polymer). Furthermore, the above content (percentage) is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, even more preferably 1 part by mass or less, and may be 0.5 parts by mass or less, per 100 parts by mass of the base polymer (especially acrylic polymer).

[0083] The adhesive layer 20 may optionally contain known additives such as solvents, silane coupling agents, ultraviolet absorbers, softeners, crosslinking agents, crosslinking accelerators, tackifying resins (rosin derivatives, polyterpene resins, oil-soluble phenols, etc.), anti-aging agents, fillers, colorants (pigments, dyes, etc.), chain transfer agents, plasticizers, surfactants, antistatic agents, rust inhibitors, and antioxidants, to the extent that they do not impair the properties of the present invention. Note that only one or more of these additives may be used.

[0084] The haze of the adhesive layer 20 is preferably 3% or less, more preferably 2% or less, and even more preferably 1% or less. The above haze can be measured using a haze meter in accordance with JIS K7136. Examples of haze meters include the "NDH2000" manufactured by Nippon Denshoku Industries Co., Ltd. and the "HM-150" manufactured by Murakami Color Technology Laboratory Co., Ltd.

[0085] The shear storage modulus (shear storage modulus) of the adhesive layer 20 at 25°C is preferably 10 kPa or higher, more preferably 15 kPa or higher, even more preferably 20 kPa or higher, and particularly preferably 25 kPa or higher, from the viewpoint of ensuring the cohesive force of the adhesive layer 20. The above shear storage modulus is preferably 500 kPa or lower, more preferably 250 kPa or lower, even more preferably 100 kPa or lower, even more preferably 80 kPa or lower, even more preferably 70 kPa or lower, even more preferably 60 kPa or lower, and particularly preferably 50 kPa or lower, from the viewpoint of achieving the softness required for optical adhesive sheets for flexible device applications in the adhesive layer 20. Methods for adjusting the shear storage modulus include, for example, selecting the type of base polymer in the adhesive layer 20, adjusting the molecular weight, adjusting the blending amount, adjusting the glass transition temperature, and adjusting the degree of crosslinking. Methods for adjusting the shear storage modulus also include selecting components other than the base polymer in the adhesive layer 20 and adjusting their blending amount. The shear storage modulus of the adhesive layer is determined by dynamic viscoelasticity measurement. This measurement can be performed using the "Advanced Rheometric Expansion System (ARES)" dynamic viscoelasticity measurement device manufactured by Rheometric Scientific. In this measurement, the measurement mode is set to shear mode, the measurement temperature range is -40°C to 100°C, the heating rate is 5°C / min, and the frequency is 1 Hz.

[0086] The thickness of the adhesive layer 20 is preferably 30 μm or more, more preferably 40 μm or more, even more preferably 45 μm or more, and particularly preferably 50 μm or more, from the viewpoint of ensuring the adhesive strength of the adhesive layer 20. From the viewpoint of making the adhesive sheet Y with a release liner thinner, the above thickness is preferably 150 μm or less, more preferably 140 μm or less, even more preferably 120 μm or less, and particularly preferably 100 μm or less.

[0087] (Lightly peelable liner) Examples of materials for the light peel-off liner 30 include polyester, polyolefin, and polycarbonate. Specifically, these are the materials exemplified above as materials for the peel-off liner used in the heavy peel-off liner 10. The light peel-off liner 30 is peelably in contact with the second surface 20a of the adhesive layer 20. The surface of such a light peel-off liner 30 (the surface on the adhesive layer 20 side) is preferably subjected to a peel-off treatment. Examples of peel-off treatments include silicone peel-off treatment and fluorine peel-off treatment.

[0088] The thickness of the light-peel liner 30 is preferably 10 μm or more, more preferably 15 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring a protective function against the adhesive layer 20. The thickness of the light-peel liner 30 as a peel liner is preferably 150 μm or less, more preferably 120 μm or less, and even more preferably 100 μm or less, from the viewpoint of thinning the adhesive sheet Y with the peel liner.

[0089] Figures 3 to 8 show an example of a method for manufacturing the adhesive sheet with a release liner of the present invention using a roll-to-roll method. The above manufacturing method includes a preparation step, an outline processing step, a removal step, a film replacement step, and a cutting step.

[0090] <Preparation Steps> In the preparation step, a long work film W is prepared as shown in Figure 3. The work film W includes a long adhesive sheet X with a release liner and a carrier film C. The adhesive sheet X with a release liner is a raw sheet of single-sheet adhesive sheets Y (Figure 1). The carrier film C supports the adhesive sheet X with a release liner.

[0091] The adhesive sheet X with a release liner comprises a heavy release liner 10, an adhesive layer 20, and a light release liner 30 in this order along the thickness direction H. The adhesive layer 20 has a first surface 20a and a second surface 20b opposite to the first surface 20a. The heavy release liner 10 is in contact with the first surface 20a. The light release liner 30 is in contact with the second surface 20b. The adhesive sheet X with a release liner extends in a planar direction perpendicular to the thickness direction H.

[0092] The adhesive sheet X with a peel-off liner can be manufactured, for example, as follows. First, the above-described adhesive composition is applied to the heavy peel-off liner 10 to form a coating film. Next, the light peel-off liner 30 is bonded onto the coating film on the heavy peel-off liner 10. Then, the coating film can be dried and cured, or cured by irradiating the coating film with active energy rays. If necessary, it may also be further heated and dried. This forms an adhesive layer 20 between the heavy peel-off liner 10 and the light peel-off liner 30. The drying temperature of the coating film may be, for example, 50°C to 200°C. The drying time may be, for example, 5 seconds to 20 minutes. If necessary, the heavy peel-off liner 10 and / or the light peel-off liner 30 may be peeled off in the adhesive layer 20 thus formed to expose the adhesive surface, and a solution of a photopolymerization initiator may be applied to the adhesive surface (additional addition as described in (iii) above). It is preferable to protect the exposed adhesive surface by bonding a new heavy-release liner 10' and / or light-release liner 30' to it before the outer shape processing step described later, thereby creating an adhesive sheet X' with a release liner having a laminated structure of [heavy-release liner 10 / adhesive layer 20 / light-release liner 30'], [heavy-release liner 10' / adhesive layer 20 / light-release liner 30], or [heavy-release liner 10' / adhesive layer 20 / light-release liner 30'].

[0093] Furthermore, known coating methods may be used for coating the above-mentioned adhesive composition. For example, coaters such as gravure roll coaters, reverse roll coaters, kiss roll coaters, dip roll coaters, bar coaters, knife coaters, spray coaters, comma coaters, and direct coaters may be used.

[0094] The carrier film C is a single-sided adhesive film having an adhesive surface on one side in the thickness direction H. In the work film W, the adhesive surface of the carrier film C is bonded to the heavy-release liner 10 side of the adhesive sheet X with a release liner. Specifically, the work film W comprises the carrier film C, the heavy-release liner 10, the adhesive layer 20, and the light-release liner 30 in this order in the thickness direction H.

[0095] Furthermore, in this embodiment, the carrier film C is wider than the adhesive sheet with a release liner X in the width direction D2 (Figure 8), which is perpendicular to the flow direction D1 (Figure 8) of the work film W. The adhesive sheet with a release liner X is positioned, for example, in the center of the width direction D2 on the carrier film C. The width of the adhesive sheet with a release liner X (length in the width direction D2) is preferably 200 mm or more, more preferably 280 mm or more, and even more preferably 400 mm or more. Also, the above width is preferably 2000 mm or less, more preferably 1800 mm or less, and even more preferably 1600 mm or less. Such a work film W is then fed into the manufacturing line.

[0096] <External shape processing process> In the external shaping process shown in Figure 4, it is preferable to perform laser processing on the work film W. Specifically, a laser processing device is used to irradiate the work film W with laser light L from the light peel liner 30 side to cut the adhesive layer 20 and the light peel liner 30 on the heavy peel liner 10. As a result, in the adhesive layer 20, individualized adhesive layers 21 and a peripheral portion 22 around the adhesive layers 21 are formed. In the light peel liner 30, a light peel liner 31 on the adhesive layer 21 and a peripheral portion 32 around the light peel liner 31 are formed. Half-cut grooves G are formed in the heavy peel liner 10.

[0097] Furthermore, the external shaping process may involve performing the laser beam irradiation process once, or it may involve performing it two or more times. In particular, to ensure reliable cutting, the same area may be irradiated with laser beam multiple times at different energies.

[0098] The laser light oscillation method in the process of irradiating with the laser light described above is not particularly limited. Examples of the oscillation method include pulsed oscillation and continuous oscillation. Therefore, the laser light may be pulsed laser light or a continuous oscillation laser. Among these, from the viewpoint of suppressing thermal deformation of the laser light irradiation area, the pulsed oscillation method is preferred. That is, the laser light is preferably pulsed laser light. With pulsed laser light, ablation processing by multiphoton absorption (non-thermal processing) can be performed more easily in the irradiation area, making it easier to perform cutting processing with excellent processing quality. In this specification, unless otherwise specified, "laser light" is used as a general term that does not limit its oscillation method and includes pulsed laser light, continuous oscillation laser, etc.

[0099] Examples of laser types used for laser processing include gas lasers, solid-state lasers, and semiconductor lasers. Examples of gas lasers include CO2 lasers and F2 lasers (wavelength 157nm). Examples of solid-state lasers include titanium-sapphire lasers (wavelength 800nm), Yb:YAG lasers (wavelength 1030nm), second harmonic of Yb:YAG lasers (wavelength 515nm), Nd:YAG lasers (wavelength 1064nm), second harmonic of Nd:YAG lasers (wavelength 532nm), third harmonic of Nd:YAG lasers (wavelength 355nm), and fourth harmonic of Nd:YAG lasers (wavelength 266nm). The laser light L used in the outer shape processing step is preferably selected from the group consisting of a Yb:YAG laser (wavelength 1030 nm), a second harmonic of a Yb:YAG laser (wavelength 515 nm), a Nd:YAG laser (wavelength 1064 nm), and a second harmonic of a Nd:YAG laser (wavelength 532 nm), from the viewpoint of suppressing variations in the absorbance of each layer in the work film W and ensuring productivity by increasing the cutting speed using a high-power oscillator.

[0100] From the viewpoint of suppressing thermal deformation in the laser light irradiation area while appropriately promoting photocuring in the adhesive layer 20, ultraviolet laser light is preferred. Specifically, the wavelength of the laser light is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 248 nm or more. Furthermore, the wavelength is preferably 2500 nm or less, more preferably 1800 nm or less, even more preferably 1200 nm or less, even more preferably 1000 nm or less, even more preferably 800 nm or less, even more preferably 500 nm or less, and particularly preferably 300 nm or less.

[0101] The wavelength of the pulsed laser light described above is preferably 200 nm or more, more preferably 500 nm or more, even more preferably 800 nm or more, and particularly preferably 1000 nm or more, from the viewpoint of suppressing thermal deformation in the laser light irradiation area while appropriately generating multiphoton absorption in the light peel liner 30 and the adhesive layer 20. Furthermore, the wavelength is preferably 2500 nm or less, more preferably 1800 nm or less, and even more preferably 1200 nm or less.

[0102] The pulse width of the pulsed laser light described above is not particularly limited, but examples include femtosecond pulsed laser light, picosecond laser light, nanosecond laser light, microsecond laser light, etc., depending on the pulse width. From the viewpoint of appropriately generating multiphoton absorption in the light peel-off liner 30 and the adhesive layer 20, the pulsed laser light is preferably short-pulsed laser light (picosecond pulsed laser light or femtosecond pulsed laser light), and from the viewpoint of suppressing thermal deformation of the laser light irradiation area, it is more preferably femtosecond pulsed laser light.

[0103] The pulse width of the pulsed laser light described above is set to 100 × 10¹⁰ from the viewpoint of appropriately generating multiphoton absorption in the peel-off liner 30 and the adhesive layer 20. -15 Preferably s (100 femtoseconds) or longer, and more preferably 150 × 10⁻⁶ -15 s or more, more preferably 200 × 10 -15 It is s or more. Also, the pulse width is 60 × 10 -12 s (60 picoseconds) or less is preferred, and more preferably 20 × 10 -12 s or less, more preferably 10 × 10 -12 It is less than or equal to s.

[0104] The pulse repetition frequency of the pulsed laser light described above is preferably 50 kHz or higher, more preferably 80 kHz or higher, and even more preferably 100 kHz or higher, from the viewpoint of appropriately generating multiphoton absorption in the peel-off liner 30 and the adhesive layer 20. Furthermore, the above frequency is preferably 5000 kHz or lower, more preferably 4000 kHz or lower, and even more preferably 3000 kHz or lower.

[0105] <Removal process> In the removal process, the surrounding portions 22 and 32 are removed from the heavy peel-off liner 10 as shown in Figure 5. In the manufacturing method of the present invention, the light peel-off liner 30 and the adhesive layer 20 can be cut well without excessively cutting the heavy peel-off liner 10, so that the surrounding portions 22 and 32 can be removed smoothly.

[0106] <Film replacement process> The film replacement process includes a step of peeling off the light-peel liner 30 as shown in Figure 6, followed by laminating a long piece of light-peel liner 30. By laminating a long piece of light-peel liner 30, an extended end is formed on the light-peel liner 30, making it easy to peel off.

[0107] <Cutting process> In the cutting process, as shown in Figure 7, the long heavy peel-off liner 10 and light peel-off liner 30 are cut into individual sheets to form the individual heavy peel-off liner 11 and light peel-off liner 31. Examples of cutting methods include cutting by laser irradiation and cutting by press processing (punching) using a die.

[0108] As described above, the heavy release liner 11, the adhesive layer 21, and the light release liner 31 are laminated in this order in the thickness direction H to produce individual adhesive sheets Y with release liners.

[0109] In the external shaping step of the above manufacturing method, as described above, an adhesive sheet Y with a release liner (a single-sheet adhesive sheet having an adhesive layer) is obtained by laser processing. Laser processing is suitable for continuously shaping the external form of the work film W while it is continuously flowing. Therefore, the above manufacturing method is suitable for efficiently producing adhesive sheets Y with a release liner.

[0110] The embodiments described above are provided to facilitate understanding of the present invention and are not intended to limit it. [Examples]

[0111] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by these examples.

[0112] (Preparation of acrylic oligomers) First, in a reaction vessel equipped with a stirrer, thermometer, reflux condenser, and nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a solvent was stirred at 70°C for 1 hour under a nitrogen atmosphere. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours, and then at 80°C for 2 hours. Next, the reaction solution was heated to 130°C to volatilize and remove toluene, chain transfer agent, and unreacted monomers. This yielded an acrylic oligomer (solid form). The weight-average molecular weight of this acrylic oligomer was 5100.

[0113] (Preparation of prepolymers) In a flask, a monomer mixture consisting of 71 parts by mass of n-butyl acrylate (BA), 13 parts by mass of N-vinyl-2-pyrrolidone (NVP), 13 parts by mass of 4-hydroxybutyl acrylate (4HBA), and 3 parts by mass of acryloylmorpholine (ACMO) was mixed with 0.031 parts by mass of a photopolymerization initiator (product name "Irgacure 184", 1-hydroxycyclohexyl-phenyl-ketone, manufactured by BASF) and another photopolymerization initiator (product name "Irgacure 651", 2,2-dimethoxy-1,2-diphenylethane-1-one, manufactured by BASF). The mixture was then irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a portion of the monomer components in the mixture and obtain a prepolymer composition. The ultraviolet irradiation was continued until the viscosity of the composition reached approximately 20 Pa·s. This viscosity was measured using a B-type viscometer under the conditions of rotor No. 5, rotor speed of 10 rpm, and temperature of 30°C. The resulting prepolymer composition contains a photopolymer and monomer components that have not undergone polymerization.

[0114] (Preparation of adhesive composition) Next, 100 parts by mass of the above prepolymer composition, 3 parts by mass of the above acrylic oligomer, 0.6 parts by mass of urethane acrylate oligomer (product name "UN-350", manufactured by Negami Kogyo Co., Ltd.) as a second photopolymerizable polyfunctional compound, 0.4 parts by mass of a photopolymerization initiator (product name "Irgacure 819", bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, manufactured by BASF), 0.5 parts by mass of an antioxidant (product name "Irganox 1010", manufactured by BASF), 0.2 parts by mass of a rust inhibitor (product name "BT-120", manufactured by Johoku Chemical Industry Co., Ltd.), and 0.3 parts by mass of a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to obtain an adhesive composition.

[0115] Example 1 (Making adhesive sheets) The above adhesive composition was coated onto a polyethylene terephthalate (PET) release liner (heavy-duty release liner, product name "MRF75", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) to a final thickness (thickness of the adhesive layer) of 100 μm, forming a coated layer (adhesive composition layer). Next, a PET release liner (light-duty release liner, product name "MRE75", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) was placed on the coated layer to cover the coated layer and obtain a laminate of [MRF75 / coated layer (adhesive composition layer) / MRE75]. Then, this laminate was illuminated from the top surface (MRF75 side) with a black light (manufactured by Toshiba Corporation) at an illuminance of 5 mW / cm². 2 The material was irradiated with ultraviolet light for 300 seconds. Furthermore, it was dried in a 90°C dryer for 2 minutes. This resulted in an adhesive sheet with a release liner, where both sides of the adhesive layer were protected by a release liner.

[0116] From the light peel-off liner side of the above-mentioned adhesive sheet with a peel-off liner, pulsed laser light was irradiated in the thickness direction using a predetermined Fs-IR laser to produce individual pieces of the adhesive sheet with a peel-off liner of Example 1 [heavy peel-off liner / adhesive layer / light peel-off liner]. In Example 1, a groove with a depth of 20 μm was formed in the heavy peel-off liner of the adhesive sheet with a peel-off liner. After Fs-IR laser irradiation, the light peel-off liner was peeled off. The ratio of the surface hardness measured using a nanoindenter (product name "Triboindenter", manufactured by Hysitron) in accordance with ISO 14577 at a location more than 20 μm inward from the edge face of the exposed adhesive layer, to the surface hardness measured similarly at the edge face of the adhesive layer after Fs-IR laser irradiation was 3.5. This indicates that in Example 1, the area within 20 μm inward from the cross-section of the adhesive layer was hardened.

[0117] Comparative Example 1 A peel-off liner-attached adhesive sheet [heavy peel-off liner / adhesive layer / light peel-off liner] for Comparative Example 1 was prepared in the same manner as in Example 1, except that treatment with a predetermined CO2 laser was performed instead of treatment with pulsed laser light. In Comparative Example 1, a groove with a depth of 20 μm was formed in the heavy peel-off liner of the peel-off liner-attached adhesive sheet. Furthermore, the surface hardness ratio of the peel-off liner-attached adhesive sheet of Comparative Example 1 after CO2 laser irradiation, measured in the same manner as in Example 1, was 0.28, and the edges of the cross-section of the adhesive layer were softened by the heat of the CO2 laser.

[0118] Comparative Example 2 A double-sided adhesive sheet with a release liner [heavy-release liner / adhesive layer / light-release liner] for Comparative Example 2 was prepared in the same manner as in Example 1, except that instead of processing with pulsed laser light, a press (punching) process was performed using a predetermined press machine. In Comparative Example 2, the edges of the cross-section of the adhesive layer of the adhesive sheet with a release liner were uncured, and no grooves were observed in the heavy-release liner. Furthermore, the ratio of surface hardness after press (punching), measured in the same manner as in Example 1, was 1.0.

[0119] [evaluation] The following evaluations were performed on the adhesive sheets with release liners prepared in the examples and comparative examples, and the results are shown in Table 1.

[0120] (1) Peeling force In the adhesive sheets with release liners of the examples and comparative examples, the peel force when the light-peel liner or heavy-peel liner was peeled from the adhesive layer at a 90° angle and a speed of 300 mm / min was measured using an autograph. Furthermore, for the peel force when the heavy-peel liner was peeled from the adhesive layer, the peel force after curing was also measured at a 90° angle and a speed of 300 mm / min. For each measurement, the peak value of the peel force was defined as the peak peel force, and the converged peel force was defined as the in-plane peel force. These values ​​were extracted and listed in Table 1. The ratio of the measured peak peel force to the in-plane peel force was also calculated and listed in Table 1.

[0121] [Table 1]

[0122] In the adhesive sheet with a release liner of the example, the edges of the cross-section of the adhesive layer harden, and the peak peeling force when peeling the heavy release liner from the adhesive layer is greater than the in-plane peeling force when peeling the light release liner from the adhesive layer. As a result, unintended delamination between the heavy release liner and the adhesive layer is suppressed, and the inclusion of air bubbles and deformation of the adhesive sheet are easily suppressed. On the other hand, in the adhesive sheets with release liners of Comparative Examples 1 and 2, the edges of the cross-section of the adhesive layer do not harden, so there is a high risk of air bubbles being included due to unintended delamination and deformation of the adhesive sheet.

[0123] The following describes variations of the invention according to the present invention. [Note 1] The device comprises, in this order, a heavy-release liner, a photocurable adhesive layer, and a light-release liner. The adhesive layer includes a cured region within 20 μm from the edge of the cross-section. An adhesive sheet with a release liner, wherein the relationship between the peak value of the release force (peak release force) Xc [N / 50mm] when the heavy release liner is released from the adhesive layer at a 90° angle and 300mm / min, and the in-plane release force Xb [N / 50mm] when the light release liner is released from the adhesive layer at a 90° angle and 300mm / min, satisfies Xc > Xb. [Note 2] The adhesive sheet with a release liner as described in Appendix 1, wherein the relationship between the peak release force Xc [N / 50mm] and the in-plane release force Xa [N / 50mm] when the heavy release liner is peeled from the adhesive layer at a 90° angle and 300mm / min satisfies Xc / Xa ≥ 2. [Note 3] The aforementioned peak peeling force Xc [N / 50mm] and the integrated light intensity of the adhesive layer irradiated at 3000 mJ / cm² 2The adhesive sheet with a release liner as described in Appendix 1 or 2, wherein the relationship between the peak peel force Xc' [N / 50mm] when the heavy release liner, after curing under conditions of light irradiation, is peeled from the cured adhesive layer at a 90° angle and 300mm / min, and Xc > Xc', satisfies the condition Xc > Xc'. [Note 4] The adhesive sheet with a release liner as described in any one of the appendices 1 to 3, wherein the elastic modulus of the adhesive layer at 25°C is 10 to 500 kPa. [Note 5] The adhesive sheet with a release liner according to any one of the appendices 1 to 4, wherein the heavy release liner has a half-cut groove formed along the end face of the adhesive layer, and the depth h of the half-cut groove satisfies h ≤ 0.7t with respect to the thickness t of the heavy release liner. [Note 6] The adhesive sheet with a release liner as described in any one of the appendices 1 to 5, wherein the thickness of the adhesive layer is 30 to 150 μm. [Explanation of symbols]

[0124] W Work Film X Adhesive sheet with release liner (long roll) Y Adhesive sheet with release liner (single sheet) C Carrier Film G Half-cut groove H thickness direction D plane direction D1 Flow direction D2 width direction 10, 11 Heavy peel-off liner 11A Extension end 20, 21, 22 Adhesive layer 30, 31, 32 Lightly peeling liner 31A Extension end L laser light

Claims

1. The device comprises, in this order, a heavy-release liner, a photocurable adhesive layer, and a light-release liner. The adhesive layer includes a cured region within 20 μm from the edge of the cross-section. An adhesive sheet with a release liner, wherein the relationship between the peak value of the release force (peak release force) Xc [N / 50mm] when the heavy release liner is released from the adhesive layer at a 90° angle and 300 mm / min, and the in-plane release force Xb [N / 50mm] when the light release liner is released from the adhesive layer at a 90° angle and 300 mm / min, satisfies Xc > Xb.

2. The adhesive sheet with a release liner according to claim 1, wherein the relationship between the peak release force Xc [N / 50 mm] and the in-plane release force Xa [N / 50 mm] when the heavy release liner is peeled from the adhesive layer at a 90° angle and 300 mm / min satisfies Xc / Xa ≥ 2.

3. The aforementioned peak peeling force Xc [N / 50 mm] and the integrated light intensity of the irradiation of the adhesive layer at 3000 mJ / cm² 2 The adhesive sheet with a peel liner according to claim 1 or 2, wherein the relationship between the peak peel force Xc' [N / 50mm] when the heavy peel liner, after curing under conditions of light irradiation, is peeled from the cured adhesive layer at a 90° angle and 300 mm / min, and Xc > Xc', satisfies the condition Xc > Xc'.

4. The adhesive sheet with a release liner according to claim 1 or 2, wherein the elastic modulus of the adhesive layer at 25°C is 10 to 500 kPa.

5. The adhesive sheet with a release liner according to claim 1 or 2, wherein the heavy release liner has a half-cut groove formed along the end face of the adhesive layer, and the depth h of the half-cut groove satisfies h ≤ 0.7t with respect to the thickness t of the heavy release liner.

6. The adhesive sheet with a release liner according to claim 1 or 2, wherein the thickness of the adhesive layer is 30 to 150 μm.

Citation Information

Patent Citations

  • Laminate

    JP2014076606A